2015
DOI: 10.1016/j.jacc.2015.06.1087
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise Cardiac Output Limitation in Pectus Excavatum

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…5 A study found that during exercise, patients with PE were unable to reach the stroke volumes of control patients at any intensity of exercise. 32 Accordingly, cardiac output was decreased, which led to a limitation in peak exercise capacity. 32 Exercise ability and maximum Vo 2 have been shown in some studies to be statistically significantly improved after repair of PE.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A study found that during exercise, patients with PE were unable to reach the stroke volumes of control patients at any intensity of exercise. 32 Accordingly, cardiac output was decreased, which led to a limitation in peak exercise capacity. 32 Exercise ability and maximum Vo 2 have been shown in some studies to be statistically significantly improved after repair of PE.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…32 Accordingly, cardiac output was decreased, which led to a limitation in peak exercise capacity. 32 Exercise ability and maximum Vo 2 have been shown in some studies to be statistically significantly improved after repair of PE. 5,33…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…Deconditioning is reported in 10-23% of adolescents with dyspnea and may be a significant contributing factor to dyspnea in pectus 38,39 . However several reports demonstrated cardiac filling in pectus is reduced in some patients as a result of compression by the displaced sternum on the right heart chambers or torqueing of the great vessels, thereby constraining increases in cardiac output during vigorous exercise [3][4][5]40 . Limitations of CPET in identifying precise mechanisms for exercise intolerance include specific response patterns are rarely pathognomonic and indirectly informative regarding the central hemodynamic responses to exertion.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms leading to the symptom burden in pectus patients are currently unclear. Many investigators propose the exercise intolerance in pectus is directly related to compromise in the cardiovascular response from the anatomic distortion of the chest wall [3][4][5] . In more extensive cases of pectus, the internally displaced chest wall may compress the lungs and may reduce resting lung volumes.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of an overgrowth of the chondral region with posterior displacement of the inferior part of the sternum, resulting in a concave chest deformity [1], [2]. Although PEXT is viewed as a benign condition with mainly cosmetic interest, characteristic clinical and imaging findings may occur, depending on the compression that right cardiac chambers suffer, when squeezed between the sternum and the column vertebrae [3], [4].…”
mentioning
confidence: 99%